Decoding Schopenhauer's metaphysics : the key to understanding how it solves the hard problem of consciousness and the paradoxes of quantum mechanics /: the key to understanding how it solves the hard problem of consciousness and the paradoxes of quantum mechanics. (2020) - Kastrup, Bernardo
No abstract available